PEMENUHAN KEBUTUHAN KONTRASEPSI KELUARGA MISKIN DI INDONESIA PADA MASA DESENTRALISASI (ANALISIS SDKI 2007) - Ni'mal Baroya (Jurnal Ilmu Kesehatan Masyarakat, 2011)
Indonesia has experienced an increasing in contraceptive use. However, it is not in line with a decreased unmet need for family planning. The decentralization policy for family planning may lead to lower unmet need among poor women.  This research aims to analyze impacts on decentralization policy for family planning in meeting contraceptive needs for poor households. This study was a survey panel using the Indonesia Demographic Health Survey (IDHS) of 2007. The subjects were all married women aged 15-49 years old. Data analysis used a multilevel modeling technique to assess the effect of individual and community factors on the unmet need for family planning. The unmet need in Indonesia was 9.2%, 8.6% and 9.1% for the year of 1997, 2002-2003 and 2007, respectively. Poorest women had higher odds of unmet need than richest (odds ratio, 1.4). The odds were also higher among women who never attending school, lack of contraceptive knowledge, unexposed with family planning information and problems in the access. In community level, the odds of unmet need was smaller when a woman lived in a community with higher mean of family planning knowledge. The implementation of decentralization policy on family planning was reduced the odds of unmet need for poor households in which the policy is then followed by the improvement of family planning knowledge for individual and community. Key words: contraceptive need, poor households, decentralization